The relationships between volcanism, tectonism, and hydrothermal activity on the Southern Equatorial Mid-Atlantic Ridge - Devey, Colin; German, Christopher; Haase, Karsten; Lackschewitz, Klas; Melchert, Bernd; Connelly, Douglas (Diversity of Hydrothermal Systems on Slow Spreading Ocean Ridges, 2010)
The Mid-Atlantic Ridge south of the equator is a key region for many aspects of spreading axis studies, from biogeography to ridge-hotspot interaction. Despite this, the ridge axis had, until 2004, seen little systematic study. Repeated trips to the area since then have mapped and explored some 900 km of ridge length, from 2° to 14°S. The result is complete bathymetric and side-scan coverage of the axialregion and the discovery and characterization of the first hydrothermal vents southof the equator. Such multisegment detailed and interdisciplinary coverage allows us to formulate a general model for the interplay between volcanism, tectonics,and hydrothermalism on a slow spreading ridge. The model defines three basic types of ridge morphology with specific hydrothermal characteristics: (a) a deep,tectonically dominated rift valley where hydrothermalism is seldom associatedwith volcanism and much more likely confined to long-lived bounding faults; (b)a shallower, segment-center bulge where a combination of repeated magmatic activity and tectonism results in repeated, possibly temporally overlapping periodsof hydrothermal activity on the ridge axis; and (c) a very shallow axis beneathwhich temperatures in all but the uppermost crust are so high that deformation is ductile, inhibiting the formation of high-porosity deep fractures and severely depressing hydrothermal circulation. This model is used together with satellite- derived predicted bathymetry to provide forecasts of the best places to look for hydrothermal sites in the remaining unexplored regions of the South Atlantic.
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IGM.legeo.therel